2011
DOI: 10.1038/mi.2010.69
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase adaptor Ndfip1 regulates T cell-mediated gastrointestinal inflammation and inflammatory bowel disease susceptibility

Abstract: Nedd4 family interacting protein 1 (Ndfip1) is an adaptor protein that regulates Itch, an E3 ubiquitin ligase that ubiquitylates JunB, thereby preventing interleukin (IL)-4 and IL-5 production. Mice lacking Ndfip1 or Itch develop T helper type 2 (TH2)-mediated inflammation in the skin and lungs and die prematurely. In this study we show that Ndfip1 − / − mice also develop inflammation in the gastrointestinal tract. Inflammation is characterized by infiltration of eosinophils and T cells and is accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 29 publications
5
39
0
Order By: Relevance
“…In Ndfip1-deficient animals, tissue destruction mediated by potent IL-4 producing Th2 cells has been shown to cause increased IL-6 at tissue sites, and this is thought to drive an increase in mucosal Th17 generation in vivo 34. However, it is also possible that this increase in Th17 cells may be due to a loss of Ndfip1 within the T cell lineage.…”
Section: Resultsmentioning
confidence: 99%
“…In Ndfip1-deficient animals, tissue destruction mediated by potent IL-4 producing Th2 cells has been shown to cause increased IL-6 at tissue sites, and this is thought to drive an increase in mucosal Th17 generation in vivo 34. However, it is also possible that this increase in Th17 cells may be due to a loss of Ndfip1 within the T cell lineage.…”
Section: Resultsmentioning
confidence: 99%
“…Mice that lack Ndfip1 naturally develop severe T H 2-mediated inflammation in the skin, gut and lungs, exhibit high levels of circulating IgE and die prematurely4647. To date, the contribution of mast cells to the pathology in these mice is unknown but studies focusing on T cells have identified that activated T H 2-polarized CD4 + T cells are a feature, possibly due to elevated production of IL-2, IL-4 and IL-5 (refs 46, 48), as well as an inability to exit the cell cycle to abort T-cell clonal expansion in response to self and exogenous antigens49.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking NDFIP1 develop a fatal T cell-mediated inflammatory disease associated with T cell activation, regulatory T cell dysfunction, and Th2-mediated organ pathology (Altin et al, 2014; Beal et al, 2011; Layman et al, 2017a; Oliver et al, 2006). NDFIP1 likely plays similar roles in humans, because NDFIP1 polymorphisms and ITCH deficiency are associated with inflammatory and autoimmune diseases (Ferreira et al, 2011; Franke et al, 2010; Hu et al, 2011; International Multiple Sclerosis Genetics et al, 2011; Lohr et al, 2010; Ramon et al, 2011). …”
Section: Introductionmentioning
confidence: 99%